2011
DOI: 10.1055/s-0030-1250735
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Rich in Quercetin Metabolites Induces G2/M Arrest by Upregulating PPAR-γExpression in Human A549 Lung Cancer Cells

Abstract: In this study, we incubated human A549 lung cancer cells with quercetin-metabolite-enriched plasma (QMP) obtained from Mongolian gerbils 2 h after quercetin feeding (100 mg/kg body wt/week). We investigated the effects of QMP on the growth of A549 cells and the possible mechanisms for these effects. We found that QMP but not control plasma (CP) reduced the cell growth in A549 cells. QMP led to cell cycle arrest at the G (2)/M phase by downregulating the expression of cdk1 and cyclin B. QMP but not CP or querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…Consistent with previous studies [13, 14], the present study also showed that oral administration of quercetin mainly increased quercetin metabolites, especially Q3G, in the plasma of mice. In contrast, i.p.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies [13, 14], the present study also showed that oral administration of quercetin mainly increased quercetin metabolites, especially Q3G, in the plasma of mice. In contrast, i.p.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been observed in animal studies [13, 14]. The biochemical and biophysical properties among quercetin and quercetin metabolites may be different because of structure modification [15], although some metabolites remain physiologically active [16, 17].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…It seems highly possible, since several in vitro studies have revealed that pioglitazone, a PPAR- γ agonist, induces cell differentiation [19] and several clinical studies have demonstrated that the activation PPAR- γ increases the degree of histopathological differentiation of liposarcoma [19, 20]. However, it is not the case for all neoplastic transformation, as others demonstrated that highly malignant cancer cell lines are characterized by higher expression of PPAR γ and these data suggest that PPAR γ may act in a cancer-permissive fashion [21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Cell growth was assayed as described previously by Yeh et al (31). A549 cells were seeded in 6-well plates at a density of 1x10 5 cells/well and cultured at 37˚C for 24 and 48 h. Various concentrations of ILL werethen added to the cells to reach final concentrations of 1, 5, 10, and 20 µM in the presence of FBS.…”
Section: Chemicalsmentioning
confidence: 99%